A construção da imagem operária: uma nova dimensão da análise do trabalho - Gerk, Angela Maria Marques da Cruz (1980)
The first objective of this study is an attempt to find a new dimension for the satisfactory developpment of human activities in work situations. The basic proposal is that human actions can be mentally programmed before being objectively executed, and this program cames 'from and his is a result of 'images. The 'operatory image' concept, as a psychological process which is able to allow beforehand the imaged simulation of these actions, assumes a primary meaning in this thesis. From the 'perception that all and each activity is developped which a localization space and corporal moviment owned by each one and from the need of finding a theoretical reference that would best fit the menshioned construct, were included the terms 'personal space' and 'corporal structure' as sensible to explicit the proposal relationship. Established the 'explaned concept triangle' capable to clarify some questions related 'to the binomian men-work, we began the seuvey and discussion about some of the variables probably envolved in the construction of 'operatory image'. In the last section, some formal-logic implications are proposed, considering concepts envolving from the nearest global aspect standpoint.